1997
DOI: 10.1016/s0735-1097(96)00560-8
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Angiographic Morphology and Clinical Presentation in Unstable Angina

Abstract: Recent rest pain and refractory or postinfarction UA, or both, are strongly associated with the general category of complex lesions and specifically with angiographically detected ICT and decreased TIMI flow.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0
9

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 93 publications
(39 citation statements)
references
References 30 publications
0
30
0
9
Order By: Relevance
“…In our analysis, total occlusions and intracoronary thrombus were considered complex lesions, and were not classified as separate angiographic variables. 18 The interobserver agreement for angiographic morphology was 90% and the intraobserver agreement was 93%.…”
Section: Coronary Angiography Analysismentioning
confidence: 88%
See 4 more Smart Citations
“…In our analysis, total occlusions and intracoronary thrombus were considered complex lesions, and were not classified as separate angiographic variables. 18 The interobserver agreement for angiographic morphology was 90% and the intraobserver agreement was 93%.…”
Section: Coronary Angiography Analysismentioning
confidence: 88%
“…13,17,18 In the present study, we incorporated complex morphology, intracoronary thrombus and total occlusions into the general angiographic definition of a complex lesion, as previously described by Dangas et al 18 A number of previous angiographic studies have reported that complex and thrombotic lesions are prevalent in UAP. 13,[15][16][17][18] Pathological studies of postmortem material revealed that these angiographic appearances were caused by plaque disruption with thrombosis. 14 Moreover, a recent immunohistochemical study using atherectomy specimens demonstrated that in UAP patients specimens from angiographic complex lesions had a greater percentage of macrophages than those from angiographic simple lesions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations